2005
DOI: 10.1161/01.atv.0000191637.48129.9b
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Tissue Factor Gene Are Associated With Clinical Outcome in Acute Coronary Syndrome and Expression Levels in Human Monocytes

Abstract: Objective-Tissue factor (TF) has, among other factors, a prominent role in acute coronary syndrome (ACS). Our goal was to investigate whether single nucleotide polymorphisms (SNP) in the TF gene (F3) are associated with plasma TF, risk, and outcome in patients with ACS. Moreover, we wanted to investigate the impact of associated TF SNPs on mRNA production in human monocytes. Methods and Results-In 725 patients with ACS [Fragmin and Fast Revascularization during Instability in CoronaryArtery Disease II (FRISC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 47 publications
4
58
1
Order By: Relevance
“…26 In another study, this single-nucleotide polymorphism was associated with an increase of tissue factor activity in monocytes from healthy donors after stimulation with lipopolysaccharide through higher expression of mRNA levels. 27 This may also be a mechanism resulting in a hypercoagulable state in women, which could be independent of plaque-related mechanisms. Relating to this hypercoagulability in a clinical setting, women show a higher embolic rate after CEA, 28,29 which is associated with cardiovascular complications after this surgical procedure.…”
Section: Strokementioning
confidence: 99%
“…26 In another study, this single-nucleotide polymorphism was associated with an increase of tissue factor activity in monocytes from healthy donors after stimulation with lipopolysaccharide through higher expression of mRNA levels. 27 This may also be a mechanism resulting in a hypercoagulable state in women, which could be independent of plaque-related mechanisms. Relating to this hypercoagulability in a clinical setting, women show a higher embolic rate after CEA, 28,29 which is associated with cardiovascular complications after this surgical procedure.…”
Section: Strokementioning
confidence: 99%
“…Some studies have described the role of the polymorphism +5466 A/G of the TF gene, showing that it is associated with the risk of thrombosis (Reny et al, 2004;Mälarstig et al, 2005;Morange et al, 2007;Davis and Erlich, 2008;Boles and Mackman, 2010) and a threefold increase in the risk of thrombosis in individuals that possess this polymorphism (Opstad et al, 2010a). Thus, several studies have reported the relationship between this polymorphism and regulation of TF expression and high levels of TF in cardiovascular disease (Campo et al, 2006;Undas et al, 2009;Opstad et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to clinical data, controversial results were reported about the contribution of TF promoter A/G haplotype on risk of cardiovascular events [11][12][13]15], with studies indicating lower [15], null [11,12] or higher [13] risk in carriers of the A promoter haplotype. It is worth to point out that the endpoint of these studies (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of TF in pathological processes may be modulated by genetic factors influencing TF expression and activity [11][12][13][14][15][16][17]. Common variants of the TF gene have been described, such as two haplotypes formed by the four completely concordant promoter polymorphisms C-1812T (rs958587), C-1322T (rs3761955), Del-1208Ins (rs ID not available), and A-603G (rs1361600), as reported by Arnaud [11].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation